Replication Data for: Devonian–Carboniferous extension and Eurekan inversion along an inherited WNW–ESE-striking fault system in Billefjorden, Svalbard - Koehl, Jean-Baptiste P.; Allaart, Lis; Noormets, Riko (DataverseNO, 2023)
High-resolution version of the figures in the following manuscript: "Devonian–Carboniferous extension and Eurekan inversion along an inherited WNW–ESE-striking fault system in Billefjorden, Svalbard". High-resolution versions of the figures are necessary to identify individual structures presented and discussed in the text.